The Effectiveness Of Using Instructional Videos On Linear Programming Material Towards Students' Mathematical Problem-Solving - Min Adlina (Fakultas Agama Islam Universitas Tjut Nyak Dhien, 2023)
The effectiveness of using instructional videos in enhancing students' mathematical abilities,particularly in Linear Programming, is being researched due to the low problem-solving skills ofstudents. This study is aimed at determining the effectiveness of using instructional videos onstudents' mathematical abilities. It is conducted at SMA Negeri 5 Binjai, specifically in class XIMIA 1, which consists of 36 students. The instrument utilized in this study comprises pretest andposttest questions. The procedures for using videos during the learning process are elaborated,including the appropriate validation treatment of the instruments to ensure smooth implementation of every component of the study. Data analysis employs the paired sample test.The obtained result shows a significance value of sig. = 0.000, where the value = 0.05 and thevalue of t-test = 22.57 > t-table = 1.688, hence it can be concluded that the pretest and posttestvalues differ significantly. From the test results and the fact that the post-test value is greaterthan the pre-test value, it can be concluded that teaching using instructional videos is effectivefor teaching and enhancing students' mathematical problem-solving abilities.